Religioni e ateismi: una complexio oppositorum alla base del neo-separatismo europeo (Stato, Chiese e pluralismo confessionale, 2011)
Testo della relazione svolta al Colloquio internazionale La laicità nella costruzione dell’Europa. Dualità del potere e neutralità religiosa, svoltosi in Bari il 4-5 novembre 2010 per iniziativa della Facoltà di Giurisprudenza dell’Università di Bari “Aldo Moro”, del Centre d’études internationales sur la romanité Université de La Rochelle e dell’Unità di ricerca “Giorgio La Pira” CNR – Università di Roma “La Sapienza”. Lo scritto, che sarà pubblicato negli atti del Colloquio, è destinato agli Studi in onore di Rinaldo Bertolino.SOMMARIO: 1. Il dialogo dell’Unione europea con le organizzazioni confessionali e non – 2. Il separatismo statunitense – 3. Il neo-separatismo europeo – 4. La complexio oppositorum nell’elaborazione cattolica … - 5 … e in quella secolare – 6. Il separatismo pluralistico europeo (e americano).ABSTRACTReligions and Atheisms: a Complexio Oppositorum at hearth of the European New-SeparatismThe European Union is not interested in religious phenomenon. It’s a form of separatism between State and Church. Yet the last Treaty about the Union functioning stated an “open, transparent and regular dialogue” between the Union and the Churches and the philosophical or non-confessional organizations alike. So religions and atheisms, the exact opposites, are not only recognized but also linked as complexio oppositorum. That originates a pluralistic separatism. By means of constitutional law research this paper demonstrates that this new-separatism is new for the Europe but usual for the U.S. and therefore it contributes a long way towards a rapprochement between Europe and America from the constitutional point of wiew.
Keywords: Unione europea e Consiglio d'Europa